Analisis Kerusakan Bucket Elevator M-145 Dengan Metode Fishbone Diagram - Arif Ardianto; Wilarso (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2021)
Machine failure on the M-145 bucket elevator contributed to downtime in January 2021, as much as 605 minutes or 6.75 hours, starting from January 17-20 2021 with a total of 17 production downtimes. The purpose of this study was to analyze the damage to the M145 elevator to determine the root cause of the damage and in this study used the fishbone diagram method. From the results of research conducted there was damage to the M145 elevator that the cause of the overflow was due to the peeling of the rubber coating on the top pulley of the upper motor pulley so that the belt became loose and caused friction on the conveyor belt, the tightness of the conveyor belt which was rarely checked, from the beginning of the construction of the bucket which caused the material to be indirect. lifted to the top but first stirred at the bottom so that it inhibits the speed of the bucket elevator. In preventing overflow damage on the M145 elevator machine by repairing or replacing the top pulley with a new pulley or repair by providing a good pulley rubber coating, as well as changing the direction of the elevator inlet so that the bucket is no longer stuck with raw materials